Elusidasi Filosofis Kebhinekaan Keagamaan: Refleksi Atas Pluralisme Keberagamaan Era Postmodern - Win Usuluddin (Ulumuna, 2010)
As noted in its wide history, religious pluralism has been understood and accepted variously. Elucidation on the religious pluralism in the postmodern era seems to be a necessity since religious pluralism has more than one interpretation. Religious pluralism is often seen as the same as plurality or even inclusivity, and religious relativism. This paper tries to explore the suspension of that pluralism and let the readers to examine it. Sequentially, this paper is begun with the short introduction related to religious pluralism in the West and in Islam. Furthermore, the paper tries to elaborate the relationship between religious pluralism and religious philosophy; explores religious philosophical perspective on pluralism, the certainty of plurality, the function of philosophy in religious distinction, some crucial aspects in religion, and religiosity in the postmodern era. As a closing, the writer tries to urge readers to reflect the religiosity in the postmodern era.